The History of Islamic Values Internalization in Enhancing National Morality in Indonesia - Yassirly Amrona Rosyada (Islah: Journal of Islamic Literature and History, 2021)
Islam is a religion that teaches universal values or thoughts for all nations in the world. Those values can be combined with local culture or even the whole nation. For its universal values, Islam can be accepted by people in the world. Indonesia is one of the countries which can accept and integrate Islamic values with local culture or National values. Moreover, Walisongo and Ulama spreading Islamic values in Indonesia played an important role in internalizing Islamic values. By using various methods and techniques, they internalize Islamic values in enhancing moral in Indonesia trough trading, education, Sufism, politics, culture, and arts. In conclusion, Islamic values act as a source of moral treasury of Indonesian people, a balance between religion and culture, a motivator, a dynamist, and an innovator of Indonesian people.